Functionalized Nanoscale Materials, Devices and Systems - Vaseashta, Ashok K.; Mihailescu, Ion N.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
The primary objective of the NATO Advanced Study Institute (ASI) titled “Functionalized Nanoscale Materials, Devices, and Systems for Chem. -Bio Sensors, Photonics, and Energy Generation and Storage” was to present a contemporary and comprehensive overview of the field of nanostructured materials and devices and its applications in chem. -bio sensors, nanophotonics, and energy generation and storage devices. The study has become one of the most promising disciplines in science and technology, as it aims at the fundamental understanding of new physical, che- cal, and biological properties of systems and the technological advances arising from their exploration. Such systems are intermediate in size, between the isolated atoms and molecules and bulk material, where the unique transitional characteristics between the two can be understood, controlled, and manipulated. Nanotechnologies refer to the creation and utilization of functional materials, devices, and systems with novel properties and functions that are achieved through the control of matter, atom-by-atom, molecule-by-molecule, or at a micro-mo- cular level. Advances made over the last few years provide new opportunities for scientific and technological developments in nanostructures and nanosystems with new architectures with improved functionality. The field is very actively and rapidly evolving and covers a wide range of disciplines. Recently, various nanoscale materials, devices, and systems with remarkable properties have been developed, with numerous unique applications in chemical and biological sensors, nanophotonics, nano-biotechnology, and in-vivo analysis of cellular processes at the nanoscale.
Invited Contributions -- Nanoscale Materials, Devices, and Systems for Chem.-Bio Sensors, Photonics, and Energy Generation and Storage -- Nanostructured Thin Optical Sensors for Trace Gas Detection -- X-Ray Photoelectron Spectroscopy and Tribology Studies of Annealed Fullerene-like WS2 Nanoparticles -- The Development and Application of UV Excimer Lamps in Nanofabrication -- Functionalization of Semiconductor Nanoparticles -- Flexoelectricity: A Universal Sensoric Mechanism in Biomembranes and in Chem.-Biosensors -- Carbon Nanotubes: From Fundamental Nanoscale Objects Towards Functional Nanocomposites and Applications -- Ultrashort Pulse PLD: A Technique for Nanofilm Fabrication -- Laser Ablation and Laser Induced Plasmas for Nanomachining and Material Analysis -- Photo-, Dual- and Exoelectron Spectroscopy to Characterize Nanostructures -- Laser Interaction with Nano-Spheres: Applications in Sub-Micron Particles Removal and Nanodot Array Fabrication -- Clean Fossil Fuels: Advanced Membrane Reactors -- Nanocrystalline Diamond Films for Advanced Technological Applications -- Diamond like Carbon Films: Growth and Characterization -- Fundamentals of Laser-Assisted Fabrication of Inorganic and Organic Films -- Nanoparticles of Semiconductors in Sol Gel Glasses -- Electrochemical Sensor Technology Based on Nanomaterials for Biomolecular Recognitions -- The Effects of Doping with Elements from the IIA Group on the Thermal and Electronic Properties of Amorphous Selenium -- Nanoscale Materials for Hydrogen and Fuel Cell Systems -- Application of Fe-Nanoscale Materials Useful in the Removal of Arsenic from Waters -- Nanopatterning Using the Bioforce Nanoenabler -- Electrocatalysts and Electrode Design for Bifunctional Oxygen/Air Electrodes -- General Contributions -- Preparation of Magnetic Chitosan Nanoparticles for Diverse Biomedical Applications -- Anomalous Behavior of Carbon Filled Polymer Composites Based Chemical and Biological Sensors -- Poly(n-isopropylacrylamide) (PNIPAM) Based Nanoparticles for In Vitro Plasmid DNA Delivery -- Rapid, Contactless and Non-Destructive Testing of Chemical Composition of Samples -- Synthesis and Application of Metal-Containing Silicas -- Semiconducting Gas Sensors, Remote Sensing Technique and Internet GIS for Air Pollution Monitoring in Residential and Industrial Areas -- Self-Assembled System of Semiconductor and Virus Like Nanoparticles -- Thermal Stability and Optical Activity of Erbium Doped Chalcogenide Glasses for Photonics -- XRD Study of Pulsed Laser Deposited AIN Films with Nanosized Crystallites -- Functionalization of Multi-Walled Carbon Nanotubes (MWCNTS) -- Sonochemical Synthesis of Inorganic Nanoparticles -- Novel Transparent Molecular Crystals of Carbon -- Hydrogen Microsensor Based on NiO Thin Films -- Design and Characterization of Styrene-Based Proton Exchange Membranes -- Strontium-Substituted Hydroxyapatite Thin Films Grown by Pulsed Laser Deposition -- Growing Thin Films of Charge Density Wave System Rb0.3MoO3 by Pulsed Laser Deposition -- Single Cell Detection with Driven Magnetic Beads -- Antimicrobial Properties of Titanium Nanoparticles -- CsHSO4/Nanooxide Polymer Membranes for Fuel Cell -- IV and CV Characteristics of Multifunctional Ilmenite-Hematite 0.67FeTiO3-0.33Fe2O3 -- Electrodeposition of Bi1?xSbx Nanowires as an Advanced Material for Thermoelectric Applications -- A Solid State Nano-Generator: Concept, Design and Theoretical Estimations -- Applications of Statistical Physics to Mixing in Microchannels: Entropy and Multifractals -- Synthesis and Characterization of Carbon Supported Pd and PtPd Catalysts for DMFCs -- Theoretical Study of the Adsorbed Small Molecule on Twisted Nanotubes by Atomic Scale Simulations -- The Defect Structure of Copper Indium Disulfide.
Keywords: Nanotechnology; Condensed matter; Engineering; Materials science; Optical materials; Electronic materials; Nanotechnology; Condensed Matter Physics; Engineering, general; Materials Science, general; Optical and Electronic Materials